Antithrombotic Activity in vivo of SDZ 217-766, a Low-molecular Weight Thrombin Inhibitor in Comparison to Heparin - Tapparelli, Carlo; Metternich, Rainer; Gfeller, Patrick; Gafner, Bernhard; Powling, Michael (Thrombosis and Haemostasis, 1995)
Antithrombotic potency of SDZ 217-766, a potent inhibitor of thrombin and other trypsin-like serine proteases, was studied in comparison with heparin in rat models of thrombin induced lung platelet accumulation, of thrombosis in arterio-venous shunt, and of venous thrombosis induced by tissue factor. Thrombin-induced platelet accumulation in the lung was inhibited dose-dependently by SDZ 217-766 following intravenous (i.v.) administration of 0.03 mg/kg to 0.3 mg/kg as well as by intraduodenal (i.d.) administration of 3 mg/kg and 10 mg/kg. Comparable inhibitory effects were observed with heparin at 30 IU/kg and 100 IU/kg. In the rat arterio-venous shunt, following i.v. administration of SDZ 217-766, thrombus formation was inhibited by 40% at 0.1 mg/kg, by 60% at 0.3 mg/kg and was abolished at 1.0 mg/kg whilst APTT was prolonged 1.1 fold over the control value at 0.1 mg/kg and 2.7 fold at 1.0 mg/kg. Similar inhibitory effects were observed following i.d. administration of 10 and 30 mg/kg with only marginal (1.2 to 1.8 fold) APTT elevation. In the same model, heparin administered either i.v., 30-300 IU/kg, or subcutaneously, 100 and 300 IU/kg, inhibited thrombus formation dose dependently but in contrast to SDZ 217-766, the inhibitory effect was paralleled by 5-to >10 fold APTT elevation over baseline. In the venous thrombosis model, SDZ 217-766 infused at 10 μg/kg/min and 20 pg/kg/min, reduced thrombus formation by 35% and 70%, respectively. In comparison, thrombus formation was decreased by 22% when heparin was infused at 1 IU/kg/min, and abolished at 3 IU/kg/min. At the doses tested, APTT was prolonged much less with SDZ 217-766 (1.6 to 2.7 fold over baseline) than with heparin (2.8 to >10 fold over baseline).The ability of SDZ 217-766, compared with heparin, to prevent thrombus formation with a minimum degree of anticoagulation together with its potential oral bioavailability make SDZ 217-766 an interesting candidate for the use in thrombosis prevention. For the use in thrombosis treatment, however, the restricted selectivity profile of SDZ 217-766 for thrombin over other serine proteases may limit its therapeutic potential.